Compliance With Surgical Oncology Specialty Care at a Safety Net Facility. Issue 10 (October 2021) - Silva, Trevor; Kadakia, Nikita; Aribo, Chade; Gochi, Andrea; Kim, Gi Yoon; Solomon, Naveen; Molkara, Afshin; Molina, David C.; Plasencia, Alexis; Lum, Sharon S.
Background: Social determinants of health challenge in at-risk patients seen in safety net facilities. Study design: We performed a retrospective review of surgical oncology specialty clinic referrals at a safety net institution evaluating referral compliance and times to first appointment and initiation of definitive treatment. Main outcomes measured included completion of initial visit, initiation of definitive treatment, time from referral to first appointment, and time from first appointment to initiation of definitive treatment. Results: Of 189 new referrals, English was not spoken by 52.4% and 69.4% were Hispanic. Patients presented without insurance in 39.2% of cases. Electronic patient portal was accessed by 31.6% of patients. Of all new referrals, 55.0% arrived for initial consultation and 53.4% initiated definitive treatment. Malignant diagnosis ( P < .0001) and lack of insurance ( P = .01) were associated with completing initial consultation. Initiation of definitive treatment was associated with not speaking English ( P = .03), malignant diagnosis ( P < .0001), and lack of insurance ( P = .03). Times to first appointment and initiation of definitive treatment were not significantly affected by race/ethnicity, language, insurance, treatment recommended, or electronic patient portal access. Conclusion: Access to surgical oncology care for at-risk patients at a safety net facility is not adversely affected by lack of insurance, primary spoken language, or race/ethnicity. However, a significant proportion of all patients fail to complete the initial consultation and definitive treatment. Lessons learned from safety net facilities may help to inform disparities in health care found elsewhere.